Energetický audit občanské stavby - Jankes, Filip (Vysoké učení technické v Brně. Fakulta stavební, 2018)
V diplomové práci je zpracován energetický audit občanské stavby dle platné legislativy České republiky. V teoretické části je popsáno téma fotovoltaiky. Ve výpočtové části je provedena analýza spotřeby energie pro výchozí stav a nový stav. Na závěr je zpracován samotný energetický audit. Jsou navržena úsporná opatření, sestaveny dvě varianty včetně doporučení jedné z nich.

The diploma thesis deals with the energy audit of the civil building according to the valid legislation of the Czech Republic. The theoretical part describes photovoltaics. In the calculation section is performed an analysis energy consumption for the initial state and new state. In the last part, the energy audit itself is elaborated. Saving measures have been proposed, two variants, including the recommendations of one of them.
Energy Audit of Civil Building
Keywords: Diplomová práce; energetický audit; občanská stavba; spotřeba energie; úsporná opatření; Diploma thesis; energy audit; civil building; energy consumption; saving measures